Estudio de los cambios de superficie en las zonas forestales, la vegetación natural y los espacios abiertos en la Raya Central Ibérica: el uso de modelos lineales generalizados - Jaraíz Cabanillas, Francisco Javier; Mora Aliseda, Julián; Gutiérrez Gállego, José Antonio (Geographicalia, 2014)
The paper tries to analyze and to understand changes in theforest and semi-natural areas of the “Raya Central Ibérica”, motivated by the rapid changes that it comes experiencing the socio-demographic structure and the economic activity of the cross-border spaces, which are stimulated by the new socioeconomic needs and by the changes experienced on the agricultural sector. A spatial analysis is applied to determine the principal driving forces of the forests and semi-natural areas changes. For this, different tools are in use in order to differentiate the land use and land cover changes, the driving forces and the dynamics of the landscape. The conclusions show the suitability of the employment of the information of CORINE Land Cover project, the significant selected independent variables, and the validity of the generalized linear models for the explanation of the land use and land cover change of a certain territory.
Keywords: Raya Central Ibérica; forests and semi-natural zones; changes; CORINE; generalized linear models.